2019
DOI: 10.1016/j.drugpo.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Stigma towards people who use drugs: A case vignette study in methadone maintenance treatment clinics in China

Abstract: Background: Drug use stigma among service providers has been recognized as a barrier to improving the accessibility and outcomes of addiction treatment. This study examined the stigmatizing attitudes towards people who use drugs (PWUD) among service providers in methadone maintenance treatment (MMT) clinics in China and its associated factors. Methods: The cross-sectional study used the baseline data of a randomized intervention trial conducted in China, and the data were collected from January 2012 to August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A previous study reported that MMT service providers had a high-level stigma toward MMT patients (17). Communitybased social support may play a more crucial role in improving and continuing the treatment of individuals under MMT (18).…”
Section: Stigmatization Toward Mmt Patientsmentioning
confidence: 96%
“…A previous study reported that MMT service providers had a high-level stigma toward MMT patients (17). Communitybased social support may play a more crucial role in improving and continuing the treatment of individuals under MMT (18).…”
Section: Stigmatization Toward Mmt Patientsmentioning
confidence: 96%
“…The Chinese believe that using drugs is a representative of personal failure, and that cannabis can be addictive and trigger more serious drug use (Zhang & Chin, 2015). Drug using is stigmatized and perceived as a moral issue (Luo et al, 2019). As Chinese society also emphasizes morality in a collectivistic context and how it is strongly built upon social relations to which individuals always belong (Shi-xu, 2014; Zhao et al, 2021), therefore, using cannabis or any kind of drugs, which is regarded as misconduct in Chinese society, may eventually damage an individual’s social relationships and their own reputation in this collectivistic society.…”
Section: Cultural and Contextual Differences About Drug Use Between C...mentioning
confidence: 99%
“…As we can also see from Liu's research team (2009) survey, they investigated different ranges. Like Luo's (2019) team, Liu's (2009) research team study also builds on a Chinese search for ideas in the West, where multiple studies have demonstrated that methadone doses are associated with higher retention rates (Booth, Corsi, & Mikulich-Gilbertson, 2004;D'Ippoliti, Davoli, Perucci, Pasqualini, & Bargagli, 1998;Faggiano, Vigna-Taglianti, Versino, & Lemma, 2003;Strain & Stitzer, 1999). In the specific investigation by Liu's team, methadone doses of less than 45 mg were notassociated with retention rates, and increasing the dose beyond 45 mg was significantly associatedwith a gradual decrease in withdrawal time.…”
Section: Theoretical Commitmentmentioning
confidence: 99%